Pengaruh Pola Permukaan pada Absorption Coefficient Material Aluminium - Aphar, Takdir Mutahli; Balfas, Muhammad; Kamil, Kusno (Universitas Pahlawan Tuanku Tambusai, 2025)
When planning a building, indoor noise levels also need to be considered. Noise is unwanted sound. The World Health Organization (WHO) considers 70 dBA to be the maximum safe noise level in the workplace. Aluminum is a chemical element in group IIIA of the periodic table, with atomic number 13 and atomic weight 26.98 grams per mole (amu). Acoustic material is a material that can absorb sound coming from a sound source. Sound is a mechanical rotational wave in air or a solid object that can still be detected by the normal human ear with a frequency range of between 20-20,2000 Hz that propagates through solid, liquid, and gaseous media that can be detected by the human senses. Absorption coefficient is the change of energy from sound energy into heat or heat energy. The quality of soundproofing material is indicated by the value of α (the absorption coefficient of the material against sound), the greater α, the better it is used as a soundproofing. Of the three best specimens, namely aluminum Aluminum without holes max value 0.10, the average value obtained is 0.10 and the min value obtained is 0.10. Of the four best specimens, namely aluminum with a depth of 4 mm diameter 6 mm 0.11 and aluminum 6 mm diameter 12 mm of 0.10 and without holes 0.10. Having two of the best specimens at a thickness of 8 mm so that aluminum with the most effective sound attenuation ability is aluminum with a diameter of 6 mm with a depth value of 4 mm and 6 mm. Key words: aluminum, depth and diameter.